Countering cybercrime in a criminal law perspective: the challenges of law enforcement in the digital age - Angga Aldilla Gussman; Raudhotul Jannah (Journal of Strafvordering Indonesian, 2026)
The development of information technology has given birth to cybercrime as a form of modern criminality that challenges the foundations of conventional criminal law. Cybercrime is not only non-territorial and complex, but also has a broad impact on the public, economic, and security interests of the country. This research aims to analyze the normative construction of cybercrime in the Indonesian criminal law system, examine the harmonization of its regulation between Law Number 19 of 2016 concerning Electronic Information and Transactions and Law Number 1 of 2024 concerning the Criminal Code, and identify the challenges of criminal law enforcement in the digital era. The research method used is normative juridical with a legislative, conceptual, and systematic approach. The results of the study show that cybercrime regulation still faces the problem of unclear formulation of delicacies, fragmentation of norms, and potential disharmonization between sectoral laws and national criminal law codification. In addition, cyber criminal law enforcement is faced with electronic proof constraints, limited capacity of the apparatus, and the complexity of cross-border jurisdictions. This condition creates a gap between the normative goals of criminal law and law enforcement practices. Therefore, it is necessary to harmonize and integrate more comprehensive cybercrime regulations so that criminal law is able to provide legal certainty, justice, and human rights protection in a balanced manner in the digital era